The Snakes And Ladders Game As A Way To Grow Moral Behavior For Children During A Pandemic Covid 19 - Lita Ariani (UMBanjarmasin, 2021)
The current Covid 19 pandemic is a frightening specter for all of humanity at this time, and Indonesia is not immune from the dangers and impacts of covid 19. One of the impacts felt is the large-scale implementation carried out by the government, including outdoor activities such as in the world of education where children are required to work bravely from their respective homes. Going to school boldly not only has positive things, but also negative ones is a gap for some children to be open with gadgets outside of school assignments. Surely the use of this gadget can have an impact on the formation of a child's character. Children can misuse gadgets and have the potential to cause addiction. One of the negative effects when children are exposed to gadgets is a change in children's behavior. During this pandemic, it is easy for parents to think creatively so that their children are not easily exposed to gadgets. Providing educational games is one way that parents can do to foster moral behavior that is starting to be eroded by gadget media. The method that will be used in this research is psychoeducation through the game of snakes and ladders.